Dangerous liaisons? An empirical assessment of inflation targeting and exchange rate regimes - Horacio Aguirre; Tamara Burdisso (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2008)
The role of the exchange rate under inflation targeting (IT) remains an unresolved issue in literature and policy discussions -and a challenge for central banks implementing IT, especially in developing countries. This paper aims at assessing whether there is a relation between the nominal exchange rate regime and inflation performance in IT countries. We use a panel of 22 countries that adopted IT between 1990 and 2006, and estimate models in order to determine whether an exchange rate regime that differs from a pure float entails higher or lower inflation. We use two de facto foreign exchange regime classifications (Levy-Yeyati and Sturzenegger, 2005; Reinhart and Rogoff, 2004), and a de jure one (IMF). We estimate regressions through methods that account for the dynamic character of the panel ('difference' and 'system' GMM estimators). We deal with potential endogeneity between inflation performance and exchange rate regime choice through the use of instrumental variables. In order to check the robustness of the results, we use alternative specifications -by including different macroeconomic control variables-, and introduce changes in the sample -by using a balanced and an unbalanced panel-. Our results suggest that the choice of exchange rate regime matters for IT countries: de facto arrangements that are less flexible than pure floats appear to deliver lower inflation, especially in developing countries. This is consistent with the fact that those countries have higher pass through coefficients and are more prone to the kind of problems dubbed as 'fear of floating'.
Keywords: E52; F31; F41; 330; inflation targeting; foreign exchange regimes; dynamic panel data; Wechselkurssystem; Inflation; Inflationssteuerung; Welt